Hidden areas of endemism: Small units in the South-eastern Neotropics. Issue 5 (4th July 2019) - Apodaca, María José; Katinas, Liliana; Guerrero, Elián Leandro
Abstract : This study aimed to establish if the Lower Río de la Plata Basin (LRPB) wetlands can be considered a biogeographic unit. The species of this area were compiled and segregated according to the habitat, selecting only 87 endemic taxa restricted to the LRPB and linked to wetlands. Distributional data of species obtained from the literature, web databases, biological collections, and field trips were georeferenced. The areas of endemism were established as those areas where the distribution of two or more taxa overlaps in groups of rivers' sections with geographic continuity and were tested with a cluster analysis. This congruence is due to ecological, geomorphological, and historical factors. Four areas of endemism were found: a broad area that comprises the whole study area (Riverine district), which is divided into three nested smaller areas (Paraguay–Paraná Flooding Valleys, Uruguay Basin, and Paraná Delta subdistricts). Then, we analysed 170 taxa distributions to evaluate the relationship between the study area and the neighbouring biogeographic units. According to the results, the study area belongs to the Paraná biogeographic province. Some areas of endemism are hidden inside broader areas and are hardly detected with the currently used biogeographic grid-methods. We propose to combine the information about ecological requirements of each taxon with its georeferenced records to estimate their areas of distribution as a primary step for searching areas of endemism in intracontinental studies.